Hypoxia-induced p53 modulates both apoptosis and radiosensitivity via AKT - Leszczynska, Katarzyna B; Foskolou, Iosifina P; Abraham, Aswin G; Anbalagan, Selvakumar; Tellier, Céline; Haider, Syed; Span, Paul N; O'Neill, Eric E; Buffa, Francesca M; Hammond, Ester M (The Journal of clinical investigation, 2015)
Restoration of hypoxia-induced apoptosis in tumors harboring p53 mutations has been proposed as a potential therapeutic strategy; however, the transcriptional targets that mediate hypoxia-induced p53-dependent apoptosis remain elusive. Here, we demonstrated that hypoxia-induced p53-dependent apoptosis is reliant on the DNA-binding and transactivation domains of p53 but not on the acetylation sites K120 and K164, which, in contrast, are essential for DNA damage-induced, p53-dependent apoptosis. Evaluation of hypoxia-induced transcripts in multiple cell lines identified a group of genes that are hypoxia-inducible proapoptotic targets of p53, including inositol polyphosphate-5-phosphatase (INPP5D), pleckstrin domain-containing A3 (PHLDA3), sulfatase 2 (SULF2), B cell translocation gene 2 (BTG2), cytoplasmic FMR1-interacting protein 2 (CYFIP2), and KN motif and ankyrin repeat domains 3 (KANK3). These targets were also regulated by p53 in human cancers, including breast, brain, colorectal, kidney, bladder, and melanoma cancers. Downregulation of these hypoxia-inducible targets associated with poor prognosis, suggesting that hypoxia-induced apoptosis contributes to p53-mediated tumor suppression and treatment response. Induction of p53 targets, PHLDA3, and a specific INPP5D transcript mediated apoptosis in response to hypoxia through AKT inhibition. Moreover, pharmacological inhibition of AKT led to apoptosis in the hypoxic regions of p53-deficient tumors and consequently increased radiosensitivity. Together, these results identify mediators of hypoxia-induced p53-dependent apoptosis and suggest AKT inhibition may improve radiotherapy response in p53-deficient tumors.